Information System Analysis at SMAN 1 Ajibarang Using COBIT 4.1 - Asiah Jayanti; Resad Setyadi (SISFORMA, 2023)
The Role of Information Systems (IS) in Information Technology Governance (ITG) has an important role in high school (SMA) educational institutions. ITG becomes very important for educational institutions in discussing the assessment of the correlation between Information Technology (IT) investment and business in each school. State Senior High School (SMAN) 1 Ajibarang has problems with academic service software for student operations and teacher administration needs. IT investment and best services in accessing the needs of teachers and students are important references about school business. The purpose of this study was to analyze IS risk management at SMAN 1 Ajibarang school using the Control Objective for Information and Related Technology (COBIT) 4.1 Framework. This study uses quantitative research methods by distributing questionnaires to respondents to obtain data on validity and reliability tests for good results. The results of the analysis show that the value of the maturity level shows at level 3, which means the value is in the defined process position. The process of achieving its goals in a much more organized manner using organizational assets is well defined. The recommendation of this research is the need for repairing network installations at SMAN 1 Ajibarang and updating administrative software for teachers and students.